2022
DOI: 10.1155/2022/7426601
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Motivation on Eating Disorders in Bodybuilders in Social Networks: The Mediating Role of State Anxiety

Abstract: The aim of this study is to explore the relationship between exercise motivation and eating disorder and the mediating effect of anxiety in physical exercise. Athletes are in a social network, and the different human-machine relationships and situations generated in this may produce different sports motivations and anxiety states for athletes. The exercise motivation, status-trait anxiety, and eating disorder of 1076 fitness subjects were described and analyzed by questionnaire survey, and the survey data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Among the motivators associated with the consumption of a food product, we can mention nutritional value, versatility, health benefits, body weight, taste/texture, religion, culture, social-ization, cost or agricultural sustainability [47,48]. Regarding physical exercise, in some cases it has been noted that motivation to exercise has a significant positive correlation with state anxiety and eating disorders [49]. Additionally, a systematic review concluded that the most prevalent motives in adults that perform recreational running were physical health, psychological motives, and personal achievement [50].…”
Section: Discussionmentioning
confidence: 99%
“…Among the motivators associated with the consumption of a food product, we can mention nutritional value, versatility, health benefits, body weight, taste/texture, religion, culture, social-ization, cost or agricultural sustainability [47,48]. Regarding physical exercise, in some cases it has been noted that motivation to exercise has a significant positive correlation with state anxiety and eating disorders [49]. Additionally, a systematic review concluded that the most prevalent motives in adults that perform recreational running were physical health, psychological motives, and personal achievement [50].…”
Section: Discussionmentioning
confidence: 99%
“…Snyder (1990) and others stated in their study that psychological self is positively correlated with exercise, and that compared to those who do not exercise, those who participate in physical activity on a regular basis will have more positive selfperceptions and evaluations would be more positive. And this positive appraisal leads to an effective reduction in the risk of developing eating disorders and alleviates clinical symptoms in people with eating disorders [28]. This perspective stems largely from the empirical evidence that physical activity plays a positive and protective role in promoting healthy behaviors and reducing risky behaviors in adolescents [29].…”
Section: Current Status Of Foreign Studies On the Correlation Between...mentioning
confidence: 99%